A Quality Improvement Initiative to Reduce the Need for Mechanical Ventilation in Extremely Low Gestational Age Neonates - Templin, Ludivine; Grosse, Camille; Andres, Virginie; Robert, Clotilde Des; Fayol, Laurence; Simeoni, Umberto; Boubred, Farid (American Journal of Perinatology, 2017)
Objective Limiting early intubation and mechanical ventilation in extremely low gestational age neonates (ELGAN) may decrease neonatal morbidity and mortality. The aim of our study was to demonstrate the feasibility, efficacy, and tolerability of a delivery room respiratory management protocol, including delayed umbilical cord clamping (DUCC) in combination with optimized nCPAP with high PEEP levels and less invasive surfactant administration (LISA).Study Design This cohort quality improvement study analyzed the respiratory and neonatal outcomes of all consecutive infants born between 24+0 and 26+6 weeks' gestation before (period 1, n = 40) and after (period 2, n = 52) implementing the new protocol.Results Compared with the period 1 infants, the period 2 infants had a lower rate of intubation in the delivery room (31 vs. 90%, p = 0.001) and were less likely to need mechanical ventilation on day 3 (28 vs. 62%, p = 0.002) and during the hospital stay (75 vs. 92.5%, p < 0.05). The two groups did not differ in terms of mortality or neonatal morbidity.Conclusion A delivery room respiratory management protocol based on DUCC, optimized nCPAP with high PEEP levels, and LISA procedure is both feasible and safe, and improved ELGAN respiratory outcomes.
Keywords: extremely low gestational age neonates; respiratory distress syndrome; nasal continuous positive airway pressure; surfactant; less invasive surfactant administration; bronchopulmonary dysplasia; delayed umbilical cord clamping